2022
DOI: 10.1002/jmv.28057
|View full text |Cite
|
Sign up to set email alerts
|

Production of single‐cycle infectious SARS‐CoV‐2 through a trans‐complemented replicon

Abstract: Single‐cycle infectious virus can elicit close‐to‐natural immune response and memory. One approach to generate single‐cycle severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) is through deletion of structural genes such as spike (S) and nucleocapsid (N). Transcomplementation of the resulting ΔS or ΔN virus through enforced expression of S or N protein in the cells gives rise to a live but unproductive virus. In this study, ΔS and ΔN BAC clones were constructed and their live virions were rescued by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…2A and B ). To further scrutinize the effect of Nsp1 on SARS-CoV-2 replication specifically, an S-deficient SARS-CoV-2 replicon (ΔS replicon) was employed ( 32 ). The ΔS replicon was transfected into VeroE6-TMPRSS2 cells, and vRNA samples were harvested on days 0, 1, and 2 for RT-qPCR of dsRED gene copies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A and B ). To further scrutinize the effect of Nsp1 on SARS-CoV-2 replication specifically, an S-deficient SARS-CoV-2 replicon (ΔS replicon) was employed ( 32 ). The ΔS replicon was transfected into VeroE6-TMPRSS2 cells, and vRNA samples were harvested on days 0, 1, and 2 for RT-qPCR of dsRED gene copies.…”
Section: Resultsmentioning
confidence: 99%
“…The grid was then washed with ddH 2 O droplet and excess liquid was removed by filter paper. The grid was then dried by air and examined with FEI TeCnai G2 20 scanning TEM at 100 kV ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…It enabled us to measure HiBiT luminescence without cell lysis. Other groups reported that replicons lacking only the S gene are applicable to the production of single-cycle infectious particles by the trans-complementation of the SARS-CoV-2 spike or other viral surface glycoproteins, such as the vesicular stomatitis virus glycoprotein (Cheung et al, 2022; Malicoat et al, 2022). The further application of our Δorf2 replicon to the production of single-cycle virus is of interest.…”
Section: Discussionmentioning
confidence: 99%